Extinction and Positivity for the Non-Newtonian Polytropic Filtration Equation (Journal of Partial Differential Equations, 1996)
The aim of this paper is to discuss the extinction and positivity for the non-Newtonian polytropic filtration equation \frac{∂u}{∂t} = \frac{∂}{∂x}(|\frac{∂u^m}{∂x}|^{p-2}\frac{∂u^m}{∂x}) with m > 0, p > 1.
Keywords: Quasilinear degenerate parabolic equations; extinction and positivity